SISTEM MANAJEMEN MUTU ISO PADA LEMBAGA PENDIDIKAN DAN PELATIHAN - Juwarini Juwarini (Jurnal Akuntansi Indonesia, 2015)
The objective of research is to understand and to analyze the influence of Leader Commitment, Consistency, Auditor Competency and Documentary Control on the implementation of Quality Management System ISO 9001:2008. Research is conducted against the employee of Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Bidang Otomotif dan Elektronika (PPPPTK BOE)/ VEDC Malang. In theoretical way, the benefits of research include giving important guide to improve the insight of managerial review and to give contribution to the developer and the implementer of ISO, and providing a reference material for the next researcher who will examine the managerial scope of ISO, especially that discuss about Leader Commitment, Consistency, Auditor Competency and Documentary Control.Practical benefit of research involves giving input and information to the management of PPPPTK/VEDC Malang to be processed, developed and applied in the planning and the implementation of Quality Management System ISO to improve the quality.Research is located at PPPPTK/VEDC, Teluk Mandar Street of Arjosari Malang. There are 40 respondents selected from 66 populations. Data are collected through questionnaire. The data are tested for its validity, reliability and others. Questionnaire is self-filled by respondent. Research method is survey with descriptive analytical approach. The analysis tool is multiple regression analysis to understand the influence of each variable. Of four independent variables analyzed simultaneously and partially, the variable with the most dominant effect is looked for. Result of research indicates that Leader Commitment, Consistency, Auditor Competency and Documentary Control, have significant influence on the implementation of Quality Management System ISO 9001:2008, either simultaneous or partial. The variable with the most dominant effect is Consistency. It is evident because consistency can improve the implementation of Quality Management System ISO 9001:2008 at Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Bidang Otomotif dan Elektronika (PPPPTK BOE)/ VEDC Malang.